Cucurmin, anticancer, & antitumor perspectives: A comprehensive review. Issue 8 (24th May 2018) - Imran, Muhammad; Ullah, Azmat; Saeed, Farhan; Nadeem, Muhammad; Arshad, Muhammad Umair; Suleria, Hafiz Ansar Rasul
ABSTRACT: Cucurmin, a naturally yellow component isolated from turmeric, ability to prevent various life-style related disorders. The current review article mainly emphasizes on different anticancer perspectives of cucurmin, i.e., colon, cervical, uterine, ovarian, prostate head and neck, breast, pulmonary, stomach and gastric, pancreatic, bladder oral, oesophageal, and bone cancer. It holds a mixture of strong bioactive molecule known as cucurminoids that has ability to reduce cancer/tumor at initial, promotion and progression stages of tumor development. In particular, these compounds block several enzymes required for the growth of tumors and may therefore involve in tumor treatments. Moreover, it modulates an array of cellular progressions, i.e., nitric oxide synthetase activity, protein kinase C activity, epidermal growth factor (EGF) receptor intrinsic kinase activity, nuclear factor kappa (NF-kB) activity, inhibiting lipid peroxidation and production of reactive oxygen species. However, current manuscript summarizes most of the recent investigations of cucurmin but still further research should be conducted to explore the role of curcumin to mitigate various cancers.